ANALISIS KASUS KEMISKINAN DI PROVINSI KALIMANTAN TENGAH DENGAN PENDEKATAN PRINCIPAL COMPONENT ANALYSIS - Annisa Halida; Nadya Farah Pradita; Yuana Sukmawaty (AL-QARDH, 2020)
According to a report by the Central Statistics Agency, the percentage of poor people in urban areas in September 2019 was 6.89%. Meanwhile, the percentage of poor people in rural areas in September 2019 was 13.10%. The data above is only a national percentage, there are still many provinces that have a poverty percentage above the national percentage, especially in Central Kalimantan Province. There are many factors that influence poverty, including education, employment status, working sector, and per capita income. This paper focuses on a study to determine the factors that have the greatest influence on poverty in Central Kalimantan Province in 2019. The results of this study simplify the poverty factor into 2 (two) factors, namely the first factor consisting of variables of education, work status, and sector. work. Meanwhile, the second factor consists of the variable per capita income for food. In addition, the greatest eigen value was obtained in the education variable of 465.67, which indicates that the education variable has the greatest influence on poverty in Central Kalimantan Province in 2019.